Dining out, the missing food consumption in China. Issue 15 (12th October 2016) - Bai, Junfei; Zhang, Caiping; Wahl, Thomas; Seale Jr., James
ABSTRACT: Food security concern in China is also the world's concern. Studies on food consumption in the past, however, often neglected the increasing food consumed away from home (FAFH). Drawn on a survey data recently conducted in nine cities by a week-long diary method, we found that FAFH in urban China accounts for a significant proportion of total food consumption, although its share varies by food category. With substantial expected income growth, overall FAFH consumption will likely continue to rise, but would be negatively affected by the rapid societal aging process, both in dining out probability and per capita consumption level. The main findings of this study have implications for food processing and service industries as well as for studies in food-related environmental issues.